A Case study of sixth form economics students, increasing the level of student creativity, stimulating student acceptance with the use of flipped learning: Kajian kes pelajar ekonomi tingkatan enam peningkatan tahap kreativiti pelajar merangsang penerimaan pelajar dengan penggunaan flipped learning - Vijayakumaran, Raja Kumari; Ismail, Ramlee; Abdul Jalil, Norasibah (Jurnal Pendidikan Bitara UPSI, 2023)
Education based on technolgy most welcome in 21century learning to produce creative and quality generation. In the 2015 Education Development Plan recommended the use of technology in education and improves student’s critical thinking skills. To stimulate critical thinking skills, learning skills based on techology be encouraged. Flipped learning method  is one of using techology as teaching aids and suit to now a days and able to attract student interest at the same time stimulate students creativy.Incresed in student’s creativy creates more success student’s. Flipped learning also known as upside down of the classroom method. This method focuses on students’ involvement and teacher became as facilitator. Learning should go on anywhere and anytime. This method is student’s dream technique in learning process now a days. In this method teacher become as student’s facilitator to student refer if they got doubt and student involvement will be more and give their ideas as well. In these studies, learning happen before, during and after by implementing flipped learning method to encourage student creativity level in school based. The objective of this studies to identify student’s creativity level, stimulate the acceptance of economics students by using FL method between FL groups and conventional group also known as traditional method and increasing of students achievement by using FL. Quantitative quasi -experimental methods were used. To evaluated student’s achievement pre and post-test question be given. To evaluated student creativity and acceptances of teaching method, pre and post questionnaire be given with 5 Likert scales was used the control group which apply conventional method and treatment groups which apply flipped learning method. There are 6 questions for creativity and 5 question for students’ acceptance of their teaching method involve 44 student’s as respondent of the studies. By using Statistical Packages for Social Science (SPSS) version 26.0 data been analysed.  The results of the study were analysed using Pearson Correlation, standard deviation and mean. The results show increased of student’s creativity level and student acceptance by implementation of FL compared to conventional method. At the same time student achievement also shows developments. This article provides space for future research by identifying the FL method and the gaps. This article serves as a reference for future studies regarding FL on teaching economics.